The Shadow of FUD: Examining Fear, Uncertainty, and Doubt in the Cybersecurity Landscape - Vishwakarma, Love (Journal of Advanced Research in Electronics Engineering and Technology; Vol 12 No 1&2 (2025): Journal of Advanced Research in Electronics Engineering and Technology, 2025)
The paper examines the use of Fear, Uncertainty, and Doubt (FUD) as a psychological tactic in the cybersecurity landscape. It explores the anatomy of FUD, detailing how it amplifies uncertainty, generates fear, and sows doubt, exploiting inherent anxieties and knowledge gaps. The mechanisms of FUD deployment, including technical jargon, exaggerated threat assessments, and social engineering, are analysed. The paper investigates the impact of FUD on individuals and organisations, such as irrational decision-making, overspending on security, and erosion of trust. Ethical considerations surrounding the use of FUD, including manipulation, misinformation, and exploitation of fear, are discussed. Finally, strategies to counter FUD, such as cultivating critical thinking, seeking reliable information, and promoting transparency, are proposed to foster informed security and a resilient digital environment.